Guia de orientações na migração de sistemas de informação do ambiente monolítico para ambiente de microsserviços na computação em nuvem em microempresas de software - Souza, Wilians Douglas Conde (2023)
The increasing use of comprehensive information systems demands that all types of information be available anywhere and anytime for effective functioning of organizations across their structures. In this scenario, the market for cloud-based enterprise application software has surpassed that of software installed on local and centralized computers. However, software microenterprises, which represent 48% of the Brazilian market, face financial constraints, lack of qualified personnel, resilience, and flexibility, making it difficult to correctly adopt new software architectures such as microservices in cloud computing. In this context, this study aimed to develop a guidance framework to support Brazilian software microenterprises in migrating information systems developed in monolithic architecture to microservices-based architecture in cloud computing. The study applied scientific methods such as systematic literature review and field research, using a questionnaire as an instrument. The main contributions of this study are the development of a guidance framework with directions extracted from the literature and selected through the application of the ABC Curve, and the validation of these directions by experts through the controlled Delphi survey method. By presenting the constraints faced by software microenterprises and providing practical guidance, it is expected that this framework will facilitate the adoption of microservices architecture in cloud computing by these companies, enabling them to evolve and adapt to market demands.